2018
DOI: 10.3390/antiox7050067
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Rigenase®, a Specific Aqueous Extract of Triticum vulgare

Abstract: Reactive species of oxygen (ROS), responsible for oxidative stress, accumulate in various tissues damaged by burns, decubitus ulcers, and vascular lesions. Antioxidants play an important and well-documented role in healing of chronic and acute wounds. Rigenase®, a specific extract of Triticum vulgare manufactured by Farmaceutici Damor, is employed in products used for the regeneration of tissue injuries. In this work, we show that Rigenase® exhibits a scavenging effect toward free radicals, thus pointing to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…An increase of actin polymerization has been linked to an increase in cell migration on wound edge and an improvement of wound contraction. By increasing the level of polymerized actin in fibroblasts, TVE could regulate the proliferative and remodeling phases of wound healing, accelerating the ability of fibro-blasts to repair the damage [9]. In 2018, Sanguigno, et al demonstrated that TVE also exerts anti-inflammatory properties since it reduces the release of the well-known agents triggering the inflammatory process, such as IL-6, TNFα, prostaglandin E2 and nitric oxide in LPS-stimulated BV2 microglial cells and in primary rat microglia, thus exerting an anti-inflammatory activity and favoring the transition from the inflammatory to regenerative process [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of actin polymerization has been linked to an increase in cell migration on wound edge and an improvement of wound contraction. By increasing the level of polymerized actin in fibroblasts, TVE could regulate the proliferative and remodeling phases of wound healing, accelerating the ability of fibro-blasts to repair the damage [9]. In 2018, Sanguigno, et al demonstrated that TVE also exerts anti-inflammatory properties since it reduces the release of the well-known agents triggering the inflammatory process, such as IL-6, TNFα, prostaglandin E2 and nitric oxide in LPS-stimulated BV2 microglial cells and in primary rat microglia, thus exerting an anti-inflammatory activity and favoring the transition from the inflammatory to regenerative process [12].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal cuff dehiscence usually occurs in the first weeks after surgery but can be delayed up to several years (especially in postmenopausal women). Vaginal cuff dehiscence often presents with postcoital bleeding, other vaginal spotting, or watery vaginal discharge [9].…”
Section: Introductionmentioning
confidence: 99%
“…Rigenase ® , a specific patented Triticum vulgare extract, exhibits antioxidant capacity by tissue-repairing activity and moisturizing action [ 18 ]; thus, it is used in the formulation of different medical devices—under the brand name Fitostimoline ® —with properties of accelerating tissue repair, improving the restoration of the epidermal barrier, and stimulating lipid synthesis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…as recently demonstrated, Damor TVE has a regenerating [13,14], antinflammatory [15] and anti-MMP9 activity [16], and antioxidant activity [17], which play a crucial role in the treatment of VVA. Furthermore, these recent studies suggest that Damor TVE is at least as efficacious as hyaluronic acid in favoring tissue re-epithelization and in contrasting inflammation.…”
Section: Introductionmentioning
confidence: 96%